The Tik Tok Vibe Phenomenon: A Semiotic Analysis - Mu'thia Mubasyira (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
This research was conducted to find out how semiotic analysis of the phenomenon that was happening today is called the term 'Tik Tok Vibe'. The semiotic point of view used is used to construct three elements of the value contained, namely autonomy, equity and survival through primary data obtained from the content uploaded by tik tok users. This research is descriptive qualitative research. In conducting analysis of findings, researchers use semiotic analysis to dismantle the actual ideology and objectives in the text on the screens' catch from the findings. The results obtained from this study are that the content contained in the tik tok social media applications turns out to contain three elements of value that has significant impacts for netizens, namely the value of autonomy, equity value and survival value contained in the tok vibe tik phenomenon. Through this research, netizens are expected to be able to cultivate media literacy and technology in consuming content presented in order to reduce the bad influence of this social media application.Keywords: Phenomenon; tik tok vibe; semiotics.